Applications of Intelligent Technologies in Healthcare - Khan, Fazlullah; Jan, Mian Ahmad; Alam, Muhammad (EAI/Springer Innovations in Communication and Computing, 2019)
This book covers topics related to medical practices from communications technology point of view. The book provides detailed inside information about the use of health informatics and emerging technologies for the well-being of patients. Each chapter in this book focuses on a specific development in the use of informatics in healthcare. In general, each chapter uses various emerging technologies such as Internet of Things (IoT), Big Data, Cloud computing, Wireless Body Area Networks (WBAN), for various health-related illness, such as tuberculosis, heart diseases, asthma and various epidemic outbreaks. The book is intended both for communications engineers with a healthcare focus and medical researchers. .